The torch race - Slade, William Adams, 1874-1950.
Typescript poem entitled, "The Torch Race," signed by Slade.
Forms part of: Miscellaneous Manuscripts collection.
Librarian.
Collection material in English.
Keywords: American poetry; Librarians